(untitled) (Dimensión Empresarial, 2019)
This research identifies the components that impact the perception of quality in a higher education institution. This was measured based on social recognition, differentiating factors and student expectations, data were collected in the CNA, OLE, and SNIES. Finally, structural equations were implemented to measure the impact of latent and observable variables that would form an exploratory model for measuring the perception of quality in higher education. The results show that the defined model is significant to explain the quality of the program studied